Integrating the food systems approach into policies to conserve biodiversity and address climate change in Colombia - Castro Nunez, Augusto; Perez Marulanda, Lisset (2024)
Food systems have become a critical component of the global environmental policy agenda. The most recent Conference of the Parties (COP) to the United Nations Framework Convention on Climate Change (UNFCCC) demonstrated that countries acknowledge the need for agriculture and food systems to adapt and transform in response to the climate change and biodiversity loss imperatives [1]. These discussions have underscored the need to strengthen the food system perspective in national and international goals and commitments, where it remains underrepresented. Despite calls from various organizations, such as WWF, CGIAR, and civil society, much work remains to address this gap.